Personal Financial Management Research: A Bibliometric Review - Loso Judijanto (Westscience Press, 2026)
This study aims to examine the development, trends, and intellectual structure of personal financial management research using a bibliometric approach. Data were collected from a reputable scientific database and analyzed using bibliometric tools to identify publication patterns, influential contributors, and thematic structures within the field. The results indicate that personal financial management research is strongly centered on financial decision making, financial literacy, and economic behavior, with a dominant focus on adult populations and quantitative methodologies. Over time, the field has evolved toward greater interdisciplinarity, integrating psychological factors, quality of life, and health-related issues, particularly in the context of financial vulnerability and global crises. The visualization of keyword networks reveals several major thematic clusters, including financial behavior, socio-economic conditions, psychological well-being, and methodological approaches. Despite its maturity, the field continues to expand into emerging areas such as experiential perspectives, qualitative inquiry, and the impact of digital and contextual factors on financial management practices. This study contributes by providing a systematic mapping of the literature and identifying potential directions for future research to enrich the understanding of personal financial management in a rapidly changing environment.